1997
DOI: 10.1071/bt96015
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Water Relations of Trees of Differing Leaf Phenology in a Wet - Dry Tropical Savanna near Darwin, Northern Australia

Abstract: The seasonal variation in leaf xylem pressure potential at dawn (ψdawn), leaf tissue water characteristics and daily maximum leaf conductance was measured in eight woody species in a wet–dry tropical savanna near Darwin, northern Australia, between October 1992 and October 1993. The species were Eucalyptus miniata, E. tetrodonta, E. clavigera, Xanthostemon paradoxus, Erythrophleum chlorostachys, Planchonia careya, Terminalia ferdinandiana and Cochlospermum fraseri. The species represented the major leaf phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
3
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 0 publications
9
65
3
1
Order By: Relevance
“…Values for all three Eucalyptus species are within the range reported for temperate angiosperm trees (Patiño et al 1995), and higher than those reported for other evergreen trees from savannas or dry tropical forests (Goldstein, Rada & Catalan 1987;Sobrado 1993Sobrado , 1996Sobrado , 1997. Mature eucalypt trees in savanna near Darwin are able to access subsoil moisture throughout the dry season (Myers et al 1997;O'Grady et al 1999), and consequently maintain high rates of sap flow, which are facilitated by conductive xylem. Trees from drier habitats, such as Venezuelan dry tropical forest, tend to have smaller, less conductive vessels (Tyree et al 1994).…”
Section: Leaf Loss Shoot Death and Water Statussupporting
confidence: 51%
See 2 more Smart Citations
“…Values for all three Eucalyptus species are within the range reported for temperate angiosperm trees (Patiño et al 1995), and higher than those reported for other evergreen trees from savannas or dry tropical forests (Goldstein, Rada & Catalan 1987;Sobrado 1993Sobrado , 1996Sobrado , 1997. Mature eucalypt trees in savanna near Darwin are able to access subsoil moisture throughout the dry season (Myers et al 1997;O'Grady et al 1999), and consequently maintain high rates of sap flow, which are facilitated by conductive xylem. Trees from drier habitats, such as Venezuelan dry tropical forest, tend to have smaller, less conductive vessels (Tyree et al 1994).…”
Section: Leaf Loss Shoot Death and Water Statussupporting
confidence: 51%
“…Mature trees maintain high leaf water potentials and high rates of assimilation, transpiration and leaf flushing during the dry season (Myers et al 1997;Williams et al 1997b;Myers et al 1998; O'Grady, Eamus & Hutley 1999;Eamus et al 1999). However, in saplings, leaf water potentials, stomatal conductance, transpiration and assimilation rates all decline (Prior, Eamus & Duff 1997;Prior & Eamus 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Predawn water potentials measured in this study fall within the values commonly obtained from field based studies in Eucalyptus (Myers et al, 1997;White et al, 1999;Zubrinich et al, 2000). The slight reductions in predawn water potential Ψ of 0.3-0.5 MPa observed for all species from winter to summer may indicate mild water deficit at this site in summer, as could be expected from the Mediterranean rainfall patterns.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have characterized the effects of seasonal changes in soil water availability and evaporative demand on regulation of leaf water status in woody plants from tropical savannas and other tropical and subtropical habitats (e.g. Eamus and Cole, 1997;Duff et al, 1997;Myers et al, 1997;Franco, 1998;Meinzer et al, 1999;Thomas and Eamus, 2002;McClenahan et al, 2004;Prado et al, 2004;Bucci et al, 2005). Fewer studies have focused on characterizing biophysical properties governing functional traits related to tree hydraulic architecture (e.g.…”
Section: Introductionmentioning
confidence: 99%